2003
DOI: 10.1093/qjmed/hcg138
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular damage from non-steroidal anti-inflammatory drugs

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for the management of rheumatological disorders, and as analgesics and antipyretics. Hepatotoxicity is an uncommon, but potentially lethal complication, which usually occurs within 12 weeks of starting therapy. It can occur with all NSAIDs, but appears to be more common with diclofenac and particularly sulindac. Female patients aged >50 years, with autoimmune disease, and those on other potentially hepatotoxic drugs, appear to be particularly susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 31 publications
1
89
0
4
Order By: Relevance
“…Although the risk of liver damage related to NSAID use is thought to be rare, several reviews have identified NSAIDs as the most common drugs to cause liver injury. 32,[84][85][86][87][88][89][90] The estimated incidence of NSAID-associated hepatotoxicity is between 3 and 23 per 100,000 patientyears. 87 Risk factors for NSAID-induced hepatotoxicity include P = 0.025 for ibuprofen Table 2).…”
Section: 78mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risk of liver damage related to NSAID use is thought to be rare, several reviews have identified NSAIDs as the most common drugs to cause liver injury. 32,[84][85][86][87][88][89][90] The estimated incidence of NSAID-associated hepatotoxicity is between 3 and 23 per 100,000 patientyears. 87 Risk factors for NSAID-induced hepatotoxicity include P = 0.025 for ibuprofen Table 2).…”
Section: 78mentioning
confidence: 99%
“…108 advanced age (older than 50 years), female gender, underlying autoimmune disease, and concomitant use of other hepatotoxic drugs. 90 Piroxicam, sulindac, nimesulide, and diclofenac are associated with highest risk, while ibuprofen is considered to have the most favorable safety profile among NSAIDs. 84,87 Coxibs have also been linked to liver damage; however, celecoxib appears to be associated with a low risk of injury.…”
mentioning
confidence: 99%
“…Reports of hepatotoxic effects of diclofenac (36,48,49) have raised the question whether the gene variants CYP2C8*3, CYP2C9*2,*3 or UGT2B7*2, which code for low-activity enzymes, could worsen these effects. Aithal et al (50) found no such association with CYP2C9*2 or *3 variants, but Daily et al (36) did.…”
Section: Diclofenacmentioning
confidence: 99%
“…77,100,101 The risk of this may be higher in patients receiving other potentially hepatotoxic drugs and varies between different NSAIDs, with toxicity usually developing within the first 6-12 weeks of therapy. [100][101][102] Idiosyncratic hepatotoxicity has also been reported in dogs receiving NSAIDs. 103 Severe hepatotoxicity following clinical use of NSAIDs has not been reported in cats, although this may simply reflect the lower prevalence of NSAID prescribing in this species.…”
Section: Liver Diseasementioning
confidence: 99%
“…107 However, it is recognised that the time for an ADE to develop is extremely variable, probably being dependent on the individual drug, the dose and the individual patient. In humans, hepatotoxicity is usually reported within the first 6 months of therapy, with more than 60% of cases reported in the first 3 months, 102 whereas acute renal failure is usually reported early, often within the first few days or weeks of commencing drug administration. 78 Based on appropriate use of NSAIDs in other species, the prevalence of ADEs is low in healthy patients.…”
Section: Screening During Treatmentmentioning
confidence: 99%